Drivers of shell growth of the bivalve, Callista chione (L. 1758) – Combined environmental and biological factors. (March 2018) - Purroy, Ariadna; Milano, Stefania; Schöne, Bernd R.; Thébault, Julien; Peharda, Melita
Abstract: Seasonal shell growth patterns were analyzed using the stable oxygen and carbon isotope values of live-collected specimens of the bivalve Callista chione from two sites in the Adriatic Sea (Pag and Cetina, Croatia). Micromilling was performed on the shell surface of three shells per site and shell oxygen isotopes of the powder samples were measured. The timing and rate of seasonal shell growth was determined by aligning the δ 18 Oshell -derived temperatures so that the best fit was achieved with the instrumental temperature curve. According to the data, shells grew only at very low rates or not at all during the winter months, i.e., between January and March. Shell growth slowdown/shutdown temperatures varied among sites, i.e., 13.6 °C at Pag and 16.6 °C at Cetina, indicating that temperature was not the only driver of shell growth. Likely, seasonal differences in seawater temperature and food supply were the major component explaining contrasting growth rates of C. chione at two study sites. Decreasing shell growth rates were also associated with the onset of gametogenesis suggesting a major energy reallocation toward reproduction rather than growth. These results highlight the need to combine sclerochronological analyses with ecological studies to understand life history traits of bivalves as archives of environmental variables. Highlights: Shell accretion of Callista chione (Adriatic Sea) largely occurs between March/April and December. Temperature, food availability and gametogenesis influence shell growth. Detailed knowledge of life history traits is key for paleoenvironmental reconstructions. Shell geochemical properties are required to link ecological data and shell growth patterns.